A comparison on the factors affecting the Singapore and Malaysia performance in the 2007 TIMSS - Mathematics. - Nguyen Duc, Duy. (2012)
In East Asia, Singapore and Malaysia share a common history in which Singapore used to be a part of Malaysia until 1965, which leads to many analogies in culture, population composition and education system nowadays. With many of similarities, students in both countries are expected to perform at relatively same levels. However, in the Trend in International Mathematics and Science Study (TIMSS), Singapore was ranked 3th in the mathematics test whilst its neighbour, Malaysia, ranked significantly below (20th). This paper examines many different key factors which may affect each country’s performance with the hope of unveiling the underlying reasons leading to a 119 points gap (or about 20%) between the two countries. The data were collected from 4592 students nested within 164 schools from Singapore and 4466 students nested within 150 schools from Malaysia, who participated in the mathematics TIMSS - 2007. The results show that most of the variables relating to student characteristics and family background are statistically significant (7 out of 10). The peer effects are also strong for both countries. Our further analysis suggests that while most of the difference in mean test scores between Malaysia and Singapore is explained by student, family and school characteristics, both peer effects of parents’ education and gender peer effects are not important factors contributing to the performance gap.